2022
DOI: 10.1097/meg.0000000000002344
|View full text |Cite
|
Sign up to set email alerts
|

The association between Dietary Diversity Score and odds of nonalcoholic fatty liver disease: a case-control study

Abstract: Objective There is no previous study that investigated the association between Dietary Diversity Score (DSS) and odds of nonalcoholic fatty liver disease (NAFLD). The present study aimed to examine the association between DDS and its components and NAFLD among Iranian adults. Methods In the case-control study, we enrolled 121 newly diagnosed cases of NAFLD and 122 with age, BMI and sex-matched controls. All NAFLD patients were diagnosed through ultrasonography methods by gastroenterologists. Anthropometric par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 51 publications
(67 reference statements)
0
6
0
Order By: Relevance
“…This finding is consistent with previous research that has shown an inverse association between DDS and the risk of diabetic nephropathy ( 29 ) and bladder cancer ( 30 ). In another study, by emphasizing the higher diversity scores for vegetables and fewer diversity scores for meat and refined grains, high DDS is inversely correlated with the risk of MASLD ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding is consistent with previous research that has shown an inverse association between DDS and the risk of diabetic nephropathy ( 29 ) and bladder cancer ( 30 ). In another study, by emphasizing the higher diversity scores for vegetables and fewer diversity scores for meat and refined grains, high DDS is inversely correlated with the risk of MASLD ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, confounding factors may not have been adequately adjusted to determine the independent association between dietary diversity and disease risk. Overall, increasing the diversity score of one's diet by emphasizing higher diversity scores for vegetables and fewer diversity scores for meat and refined grains may be beneficial to managing MASLD ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased dietary diversity leads to more opportunities to choose foods that are negatively associated with NAFLD. Ebrahimi et al ( 55 ) noted that dietary diversity was correlated with increased vitamin C, calcium, and fiber, all of which were negatively associated with liver disease. Furthermore, dietary diversity may increase the intake of various micronutrients, dietary fiber, and some healthful phytochemicals, which are positively associated with dietary balance ( 56 , 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there is no pharmacological therapy for NAFLD. It is obvious that lifestyle modification including diet and exercise are golden keys to fatty liver managements [ 7 8 9 10 ]. Regardless of calorie-related aspects of diet and its correlation with weight control, studies have less addressed the effects of dietary composition on liver health [ 11 ].…”
Section: Introductionmentioning
confidence: 99%